2015
DOI: 10.1109/tns.2015.2490479
|View full text |Cite
|
Sign up to set email alerts
|

Multi-MGy Radiation Hard CMOS Image Sensor: Design, Characterization and X/Gamma Rays Total Ionizing Dose Tests

Abstract: International audienceA Radiation Hard CMOS Active Pixel Image Sensor has been designed, manufactured and exposed to X and 60Co γ-ray sources up to several MGy of Total Ionizing Dose (TID). It is demonstrated that a Radiation-Hardened-By-Design (RHBD) CMOS Image Sensor (CIS) can still provide useful images after 10 MGy(SiO2) (i.e. 1 Grad). This paper also presents the first detailed characterizations of CIS opto-electrical performances (i.e. dark current, quantum efficiency, gain, noise, transfer functions, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Previous work has demonstrated that reaching a 10 MGy (1 Grad) radiation hardness with a CMOS Image Sensor (CIS) is feasible [2], [3]. In order to confirm this conclusion and to demonstrate that a full camera can also be made radiation hard up to several Mega-gray, the FUsion for energy Radiation Hard Image sensor (FURHI) and Imaging System (FURHIS) demonstrators have been developed.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Previous work has demonstrated that reaching a 10 MGy (1 Grad) radiation hardness with a CMOS Image Sensor (CIS) is feasible [2], [3]. In order to confirm this conclusion and to demonstrate that a full camera can also be made radiation hard up to several Mega-gray, the FUsion for energy Radiation Hard Image sensor (FURHI) and Imaging System (FURHIS) demonstrators have been developed.…”
Section: Introductionmentioning
confidence: 87%
“…The illumination system power and the sensor integration time will be tuned to achieve the sensitivity required by the application at the camera level. It is worth noting that the final Large voltage shifts in RHBD CIS analog readout chain due to 3.3V ELT P-MOSFETs 2 mitigation techniques proposed [2] Only use 1.8V ELT N&P-MOSFETs [3] Only use ELT N-MOSFETs (3.3V) (this work) Figure 1. Overview of the explored radiation hardening approaches for the CIS analog readout chain.…”
Section: Experimental Details a The Furhi Sensormentioning
confidence: 92%
See 3 more Smart Citations